Transcriptomic Responses of Rhizobium phaseoli to Root Exudates Reflect Its Capacity to Colonize Maize and Common Bean in an Intercropping System - Aguirre-Noyola, José Luis; Rosenblueth, Mónica; Santiago-Martínez, Michel Geovanni; Martínez-Romero, Esperanza (Frontiers in Microbiology, 2021)
Corn and common bean have been cultivated together in Mesoamerica for thousands of years in an intercropping system called "milpa", where the roots are intermingled, favoring the exchange of their microbiota, including symbionts such as rhizobia. In this work, we studied the genomic expression of Rhizobium phaseoli Ch24-10 (by RNA-seq) after a 2 h treatment in presence of root exudates of maize and bean grown in monoculture and milpa system under hydroponic conditions. In bean exudates, rhizobial genes for nodulation and degradation of aromatic compounds were induced, while in maize a response of degradation of mucilage and ferulic acid was observed, as well as the transport of sugars and iron. Ch24-10 transcriptomes in milpa resembled those of beans because they share the high expression of nodulation genes; however, some genes that were expressed in corn exudates were also induced by the intercropping system, especially those for the degradation of phenolic compounds and pectin. Beans grown in milpa system formed nitrogen-fixing nodules similar to monocultured beans, therefore, the presence of maize did not interfere with the Rhizobium-bean symbiosis. Genes for the metabolism of sugars and amino acids and the extrusion of flavonoids and phytoalexins were expressed in both monocultures and milpa system, which reveals the adaptive capacity of rhizobia to colonize both legumes and cereals. Transcriptional fusions of the putA gene, which participates in proline metabolism, and of a gene encoding a polygalacturonase were used to validate their participation in plant-microbe interactions. We determined the enzymatic activity of carbonic anhydrase whose gene was also overexpressed in response to root exudates.